2022
DOI: 10.7546/phb.28.3.2022.6
|View full text |Cite
|
Sign up to set email alerts
|

Three new Centaurea species for Albania

Abstract: During fieldwork in Korça district (S Albania) between 2019 and 2022, Centaurea devasiana, C. marmorea and C. thracica were collected and documented as new additions for the flora of Albania. Centaurea devasiana was collected in limestone pastures on Ivani Mt, Prespa National Park, c. 14 km distant from its locus classicus on Mt Devas, Greek Prespa. It had previously been considered a Greek endemic. Centaurea marmorea was found on the western rocky limestone slopes and pastures of Dry Mt (Mali i Thatë) above B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…subsp. pindicola, Narthecium scardicum, Pinguicula balcanica, Ranunculus degenii, Scilla albanica, Soldanella dimoniei and Soldanella pindicola, recorded in the shores and the belt around glacial lakes in Albania [36,37,54] might be considered as good indicators for the water quality and habitat integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…subsp. pindicola, Narthecium scardicum, Pinguicula balcanica, Ranunculus degenii, Scilla albanica, Soldanella dimoniei and Soldanella pindicola, recorded in the shores and the belt around glacial lakes in Albania [36,37,54] might be considered as good indicators for the water quality and habitat integrity.…”
Section: Discussionmentioning
confidence: 99%
“…83 glacial lakes were subject of this survey. Therefore, different plant guides were used for species and habitats determination [34][35][36][37]. A five-degree scale was used to quantify the abundance of the observed and recognized macrophyte species along transects and in the deep zone of each lake: 1 represents very rare, 2 represents rare, 3 represents common, 4 represents frequent, and 5 represents abundant [38,39].…”
Section: Methodsmentioning
confidence: 99%
“…It was described from S Albania in vicinity of Berat (Brullo et al 2019). It was also recorded from SE [Mt Galičica ("Mali i Thatë")], NW (Mali i Rencit near Shkodër) and N [Mt Paštrik ("Malin e Gajrepit")] Albania (Shuka et al 2021).…”
Section: Stachys Patulamentioning
confidence: 99%
“…Examination of that herbarium material (908 E 00799901) showed that it actually refers to A. albanicum Brullo, C. Brullo, Cambria, Giusso & Salmeri. It was also recorded from Albanian part of Mt Paštrik ["Malin e Gajrepit"](Shuka et al 2021). Comments on the presence of this species in Serbia are listed on page 70.…”
mentioning
confidence: 99%
“…Mountain tea populations have been reduced by 50 % in the Prespa area from 1990 until today, and since its population in Albania has been reduced by 30 % and destructive harvest practices of the natural population continue, it has been assessed as endangered (EN) species by the Albanian government (Shuka & Malo, 2010;MoE, 2013;Shuka et al, 2021). Furthermore, S. raeseri, with its closest relative, S. scardica, is listed as species of high conservation interest for the western Balkan countries (Aneva & Zhelev, 2018).…”
Section: Introductionmentioning
confidence: 99%